Agricultural Extension Roles and Performance Build Rice Farmer Competence: Peran dan Kinerja Penyuluh Pertanian dalam Membangun Kompetensi Petani Padi - Cahya Yuhan Armandha; Hamidah Hendrarini; Gyska Indah Harya (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Agricultural extension services actively cultivate agricultural knowledge, technical skills, and managerial capacity to support sustainable rice farming. Specific Background Growers in peri-urban areas frequently confront challenges including limited extension personnel, shrinking agricultural land, and technology adoption barriers, necessitating optimal extension delivery. Knowledge Gap Previous literature predominantly investigates extension delivery as isolated factors, leaving a scarcity of empirical evidence regarding the simultaneous predictability of these variables on grower capabilities in peri-urban settings. Aims This study investigates the concurrent operational delivery of agricultural extension workers on the capabilities of rice growers in Pertapan Maduretno Village, Sidoarjo Regency. Results Utilizing a quantitative methodology and Structural Equation Modeling-Partial Least Squares on data from 104 purposively selected respondents, the findings reveal that both the operational role and field delivery of agricultural professionals positively and significantly predict grower capabilities. Together, these structural variables account for 53.4 percent of the variance in grower capabilities. Novelty This research distinctly integrates extension operations into a unified structural model to elucidate grower capabilities within a peri-urban demographic facing specific personnel shortages and technological challenges. Implications Prioritizing practical field demonstrations, active participation, technology dissemination, capital access, and marketing support will decisively shape grower capabilities and secure sustainable agricultural development. Highlights: Field demonstrations and technology dissemination actively shape grower capabilities in peri-urban environments. Structural modeling confirms a 53.4 percent variance explanation regarding grower knowledge and technical skills. Active professional delivery mitigates challenges related to limited personnel and shrinking agrarian land. Keywords: Agricultural Extension, Structural Equation Modeling, Farmer Competence, Peri-Urban Agriculture, Sustainable Rice Farming